(untitled) - Woodfield, Brian F. (Upper Saddle River, N.J., 2006)
Contains a full virtual lab environment as well as the pre-arranged labs that are referenced in the workbook and at the end of the chapter in the textbook. Virtual ChemLab can be run directly from the CD or installed on the student’s computer.
Keywords: Chemistry,Hóa học; Experiments,Thí nghiệm